Genome-Wide Association Study Reveals Novel Genes Associated with Culm Cellulose Content in Bread Wheat (Triticum aestivum, L.) - Kaur, Simerjeet; Zhang, Xu; Mohan, Amita; Dong, Haixiao; Vikram, Prashant; Singh, Sukhwinder; Zhang, Zhiwu; Gill, Kulvinder S.; Dhugga, Kanwarpal S.; Singh, Jaswinder (Frontiers in Plant Science, 2017)
Plant cell wall formation is a complex, coordinated and developmentally regulated process. Cellulose is the most dominant constituent of plant cell walls. Because of its paracrystalline structure, cellulose is the main determinant of mechanical strength of plant tissues. As the most abundant polysaccharide on earth, it is also the focus of cellulosic biofuel industry. To reduce culm lodging in wheat and for improved ethanol production, delineation of the variation for stem cellulose content could prove useful. We present results on the analysis of the stem cellulose content of 288 diverse wheat accessions and its genome-wide association study (GWAS). Cellulose concentration ranged from 35-52% (w/w). Cellulose content was normally distributed in the accessions around a mean and median of 45% (w/w). Genome-wide marker-trait association study using 21,073 SNPs helped identify nine SNPs that were associated (p<1E-05) with cellulose content. Four strongly associated (p<8.17E-05) SNP markers were linked to wheat unigenes, which included β-tubulin, Auxin-induced protein 5NG4 and a putative transmembrane protein of unknown function. These genes may be directly or indirectly involved in the formation of cellulose in wheat culms. GWAS results from this study have the potential for genetic manipulation of cellulose content in bread wheat and other small grain cereals to enhance culm strength and improve biofuel production.